New digital cholangiopancreatoscopy for diagnosis and therapy of pancreaticobiliary diseases (with videos). (29th February 2016) - Tanaka, Reina; Itoi, Takao; Honjo, Mitsusyoshi; Tsuchiya, Takayoshi; Kurihara, Toshio; Tsuji, Shujiro; Tonozuka, Ryosuke; Kamada, Kentato; Sofuni, Atsushi; Mukai, Shuntaro
Abstract: Background: Recently, a new digital cholangiopancreatoscopy (DCPS) has been developed. The aim of this study is to retrospectively evaluate the utility of new DCPS in patients with pancreaticobiliary diseases. Methods: Digital cholangiopancreatoscopy was used in 26 patients (16 men) with pancreaticobiliary diseases that could not be diagnosed and treated by standard endoscopic retrograde cholangiopancreatography (ERCP). The procedures included DCPS‐guided tissue sampling and interventions. Technical success and adverse events were evaluated. Results: Among the 26 patients, 19 patients were classified for diagnostic purposes and seven for therapeutic purposes. The detailed breakdown of the particular conditions and numbers of patients was as follows: indeterminate bile duct (BD) lesion, indeterminate pancreatic duct (PD) lesion, lithotripsy by yttrium aluminum garnet‐laser or electrohydraulic lithotripsy, removal of migrated BD stent and PD stent, and guidewire passing across the biliary stricture. The overall technical success rates of visualizing the target lesions and therapeutic interventions were 100% and 85.7%, respectively. The incidence of procedure‐related adverse events among the patients was 7.7% (2/26). Cholangitis developed in one of the patients and post‐endoscopic sphincterotomy bleeding in one patient. All adverse events were successfully treated by conservative therapy. Conclusion: Digital cholangiopancreatoscopy has a high potential for providing an accurate diagnosis and facilitating therapy in patients with pancreaticobiliary diseases. Abstract : Highlight Tanaka and colleagues evaluated the SpyGlass TM DS Direct Visualization System in the first ever large case series of this novel digital cholangiopancreatoscopy system. Assessment of adverse event incidence and technical success rates demonstrated its promising potential for providing an accurate diagnosis and facilitating optimal therapy in patients with pancreaticobiliary diseases.